AtHMA4 drives natural variation in leaf Zn concentration of Arabidopsis thaliana - Chen, Zi-Ru; Kuang, Lu; Gao, Yi-Qun; Wang, Ya-Ling; Salt, David E.; Chao, Dai-Yin (Frontiers Media, 2018)
Zinc (Zn) is an essential element for plant growth and development, and Zn derived from crop plants in the diet is also important for human health. Here, we report that genetic variation in Heavy Metal-ATPase 4 (HMA4) controls natural variation in leaf Zn content. Investigation of the natural variation in leaf Zn content in a world-wide collection of 349 Arabidopsis thaliana wild collected accessions identified two accessions, Van-0 and Fab-2, which accumulate significantly lower Zn when compared with Col-0. Both quantitative trait loci (QTL) analysis and bulked segregant analysis (BSA) identified HMA4 as a strong candidate accounting for this variation in leaf Zn concentration. Genetic complementation experiments confirmed this hypothesis. Sequence analysis revealed that a 1-bp deletion in the third exon of HMA4 from Fab-2 is responsible for the lose of function of HMA4 driving the low Zn observed in Fab-2. Unlike in Fab-2 polymorphisms in the promoter region were found to be responsible for the weak function of HMA4 in Van-0. This is supported by both an expression analysis of HMA4 in Van-0 and through a series of T-DNA insertion mutants which generate truncated HMA4 promoters in the Col-0 background. In addition, we also observed that Fab-2, Van-0 and the hma4-2 null mutant in the Col-0 background show enhanced resistance to a combination of high Zn and high Cd in the growth medium, raising the possibility that variation at HMA4 may play a role in environmental adaptation.